Barriers to physical activity and sport participation for people with intellectual disabilities from culturally and linguistically diverse backgrounds*. Issue 2 (3rd July 2021) - Kappelides, Pam; Bould, Em; Bigby, Christine
Abstract: People with intellectual disabilities and people from culturally and linguistically diverse (CALD) backgrounds have lower rates of physical activity compared to the general population. The aim of this study was to explore physical activity among people with intellectual disabilities from CALD backgrounds, and their perceptions about the obstacles they face to participation. Ninety-one people participated in seven focus groups that discussed experiences of participation in physical activity. Six groups involved people with intellectual disabilities from CALD backgrounds and one staff group from sport, recreation or community organisations. Transcriptions of the discussions were coded inductively into themes. Participants with intellectual disabilities valued participation but were obstructed by the failure of community organisations and institutions to provide accessible information, access to appropriate resources and discriminatory attitudes of both other attendees and organisations. The findings suggest the need for multiple strategies targeted at community- based organisations and at broader institutional levels to support reasonable adjustments to include people with diverse backgrounds and abilities, and combat deep rooted racism and ableism.